2005
DOI: 10.1183/09031936.04.00030004
|View full text |Cite
|
Sign up to set email alerts
|

Changes in extracranial arteries in obstructive sleep apnoea

Abstract: Obstructive sleep apnoea (OSA) is linked with increased cardiovascular morbidity and mortality, possibly through an enhancement of atherosclerotic vascular changes. Up to now, however, only a few studies have tried to evaluate the occurrence of atherosclerosis in patients with OSA.In the present study, ultrasonography of the large extracranial vessels was performed in a group of consecutively admitted OSA patients (n535) and a control group of non-OSA patients (n535). Common carotid artery-intima media thickne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
45
0
10

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 35 publications
7
45
0
10
Order By: Relevance
“…28 However, we did not find an independent link between the severity of OSAS and carotid plaque formation, although it has been previously described. 18,19 These discordant results possibly reflect the fact that although focal atherogenesis and intima-media thickening share common risk factors they differ in nature. Atherosclerosis is a very complex and multifactorial process in nature and it is not reflected per se by IMT.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…28 However, we did not find an independent link between the severity of OSAS and carotid plaque formation, although it has been previously described. 18,19 These discordant results possibly reflect the fact that although focal atherogenesis and intima-media thickening share common risk factors they differ in nature. Atherosclerosis is a very complex and multifactorial process in nature and it is not reflected per se by IMT.…”
Section: Discussionmentioning
confidence: 50%
“…Recent studies have evaluated the effect of OSAS on most of the aforementioned arterial characteristics. [14][15][16][17][18][19][20] These studies demonstrated an increase in carotid IMT and arterial stiffness in patients with OSAS, suggesting that OSAS may promote vascular disease. However, some of these studies excluded patients with cardiovascular or cerebrovascular disease, hypertension, diabetes mellitus, hyperlipidaemia or severe obesity 17,20 and therefore were not representative of the usual population of patients with OSAS encountered in clinical practice who exhibit a high burden of cardiovascular risk factors.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…В статье содержатся результаты наблюдений за 150 больными артериальной гипертонией, их которых 75 пациентов с арте-риальной гипертонией и синдромом обструктивного апноэ сна (основная группа) и 75 больных с артериальной гипертонией без синдрома обструктив-ного апноэ (контрольная группа). В данное исследование включены пациенты с различным диапазоном индекса массы тела -от нормальных величин (18,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)9 Aim. To study an interrelation between obstructive sleep apnea syndrome with lipid metabolism disorders and atherosclerotic lesion of carotid arteries in patients with arterial hypertension.…”
unclassified